Exploring exercise, emotional eating, and body dissatisfaction in depression risk: Using structural equation modeling - Zhimin Yi; Mingtao Chen; Renzhao Huang; Weiguo Chen; Huigen Liu; Guoqiu Liu; Ming Hao (PLoS ONE, 2025)
In order to fill the relevant research gap on the influence of body dissatisfaction on depression in Chinese college students, we used structural equation modeling to explore the relationships between physical activity, body dissatisfaction, eating behavior, and depression. Participants were 1,714 undergraduate students in Southern China. Exercise served as a significant mediator between body mass index and depression, as well as between body dissatisfaction and emotional eating, accounting for 30% and 19.8% of the total effects, respectively. Emotional eating behavior mediated the relationship between exercise and depression. This study underscores the influences of body dissatisfaction on both physical inactivity and emotional eating patterns among Chinese university students. It suggests that reducing body dissatisfaction and emotional eating holds significant potential for preventing depression.